Interference in the Acquisition of the Present Perfect Continuous: Implications of a Grammaticality Judgment Test - Jason Miin-Hwa Lim (2008)
Linguistic interference in the acquisition of tenses has remained a fertile area for extensive studies on the teaching of English to speakers of other languages. Congruent with previous studies, this study aims to find out whether errors in the learning of a grammatical category is more ascribable to negative transfer resulting from learners’ first language or the rules governing its use in the target language. Employing a grammaticality judgment test in the form of an elicitation procedure, the researcher focuses on second language learners’ acquisition of the present perfect continuous in an attempt to investigate the extent to which interference may occur as a result of learners’ confusion with temporal and aspectual values that collectively form part of the learners’ mother tongue and second language. Using the data elicited, the researcher has found that linguistic interference should not be construed as merely negative transfer from the learner’s first language because temporal and aspectual values associated with verb forms in the target language itself may also be an essential component of interference. Based on the findings, the researcher has recommended a three-pronged interactive approach to the teaching of the present perfect continuous, related verbal categories, and temporal/frequency adverbials.